2019
DOI: 10.1039/c9ra09389c
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, cytotoxicity and anti-inflammatory activity of rhamnose-containing ursolic and betulinic acid saponins

Abstract: Betulinic acid and ursolic acid are ubiquitous, naturally-occurring triterpenoids exhibiting various pharmacological activities including cytotoxic and anti-inflammatory activities. However, these triterpenoids display unfavorable pharmacokinetic properties as well as low aqueous solubility. It has been shown that the presence of a-L-rhamnose moieties positively modulates the anticancer activity of secondary metabolites. Herein we report the synthesis and in vitro evaluation of cytotoxic and antiinflammatory a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 39 publications
2
18
0
Order By: Relevance
“…Immune upregulation activities were majorly evaluated in quillaic-saponins, which were extensively studied for the enhancement of serum IgG production compared to GPI-0100 and QS-21 for the development of vaccine adjuvants [47][48][49]. As for immune downregulation activities, ursane-saponins were able to protect H9c2 cardiomyocytes from H 2 O 2 -induced apoptosis in a dose-dependent manner (0.02-0.5 µg/mL) through the inhibition of ROS generation and maintenance of mitochondrial membrane potential which were possibly related to the binding of Hsp90AB1 [52,89], and prevented NO overproduction induced by lipopolysaccharides (LPSs) in macrophages with EC 50 = 9.8 µM [53]; dammarane-saponins were found to be effective in reducing serum IgE levels and airway resistance in an OVA-induced asthmatic mouse model [60]. The activity of glucosidase inhibition was evaluated in oleanane-, ursane-, and furostane-type saponins.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Immune upregulation activities were majorly evaluated in quillaic-saponins, which were extensively studied for the enhancement of serum IgG production compared to GPI-0100 and QS-21 for the development of vaccine adjuvants [47][48][49]. As for immune downregulation activities, ursane-saponins were able to protect H9c2 cardiomyocytes from H 2 O 2 -induced apoptosis in a dose-dependent manner (0.02-0.5 µg/mL) through the inhibition of ROS generation and maintenance of mitochondrial membrane potential which were possibly related to the binding of Hsp90AB1 [52,89], and prevented NO overproduction induced by lipopolysaccharides (LPSs) in macrophages with EC 50 = 9.8 µM [53]; dammarane-saponins were found to be effective in reducing serum IgE levels and airway resistance in an OVA-induced asthmatic mouse model [60]. The activity of glucosidase inhibition was evaluated in oleanane-, ursane-, and furostane-type saponins.…”
Section: Discussionmentioning
confidence: 99%
“…Legault and co-workers have demonstrated that a bidesmosidic betulinic saponin 28-O-α-l-rhamnopyranosyl betulin 3β-O-α-l-rhamnopyranoside (Bi-L-RhamBet) induced lung cancer cell death through the mitochondrial electron transfer chain which induced ROS production and decreased membrane potential, leading to apoptosis and DNA fragmentation [97]. Based on the findings, Pichette and co-workers synthesized α-L -rhamnose-containing betulinic and ursolic saponins, which exhibited cytotoxicity against human colorectal adenocarcinoma cells DLD-1 (IC 50 = 5 µM) and low toxicity in human skin fibroblasts WS-1 (IC 50 > 100 µM) in dirhamnoside-bearing betulinic derivatives (25) and anti-inflammatory activity was revealed in ursolic derivatives (26) [53]. Liberek and co-workers synthesized glucosamine-and galactosamine-containing betulinic saponins, revealing that galactosamine derivative (27) exhibited high cytotoxicity in both MCF-7 breast cancer cells and HDFa normal cells (1.7 and 4.2 µM, respectively), and had no inhibition activity toward bacteria and fungi [54].…”
Section: Lupanementioning
confidence: 99%
“…Saponins exhibit varied levels of anti-inflammatory activity, which is associated with their chemical structure [Gepdiremen et al 2005, Sylla et al 2019. As shown in a study conducted by Süleyman et al [2003], crude and purified saponin Hedera helix extracts were effective inhibitors of carrageenan-and cottonpellet-induced acute and chronic inflammation in rats.…”
Section: Anti-inflammatory Activitymentioning
confidence: 99%
“…Betulinic acid (BA) is a naturally occurring pentacyclic lupane-type triterpene [13] which has been used in folk medicine for centuries [14]. It is known to possess antiviral [15], anti-malarial [16], anti-inflammatory [17], and anthelmintic activity against Caenorhabditis elegans [18].…”
Section: Introductionmentioning
confidence: 99%